Integrated analysis of transcriptome, metabolome, and histochemistry reveals the response mechanisms of different ages Panax notoginseng to root-knot nematode infection - Wang, Zhuhua; Wang, Wenpeng; Wu, Wentao; Wang, Huiling; Zhang, Shuai; Ye, Chen; Guo, Liwei; Wei, Zhaoxia; Huang, Hongping; Liu, Yixiang; Zhu, Shusheng; Zhu, Youyong; et al. (Frontiers in Plant Science, 2023)
Panax notoginseng (P. notoginseng) is an invaluable perennial medicinal herb. However, the roots of P. notoginseng are frequently subjected to severe damage caused by root-knot nematode (RKN) infestation. Although we have observed that P. notoginseng possessed adult-plant resistance (APR) against RKN disease, the defense response mechanisms against RKN disease in different age groups of P. notoginseng remain unexplored. We aimed to elucidate the response mechanisms of P. notoginseng at different stages of development to RKN infection by employing transcriptome, metabolome, and histochemistry analyses. Our findings indicated that distinct age groups of P. notoginseng may activate the phenylpropanoid and flavonoid biosynthesis pathways in varying ways, leading to the synthesis of phenolics, flavonoids, lignin, and anthocyanin pigments as both the response and defense mechanism against RKN attacks. Specifically, one-year-old P. notoginseng exhibited resistance to RKN through the upregulation of 5-O-p-coumaroylquinic acid and key 2 genes involved in monolignol biosynthesis, such as PAL, CCR, CYP73A, CYP98A, POD, and CAD. Moreover, two-year-old P. notoginseng enhanced the resistance by depleting chlorogenic acid and downregulating most genes associated with monolignol biosynthesis, while concurrently increasing cyanidin and ANR in flavonoid biosynthesis. Three-year-old P. notoginseng reinforced its resistance by significantly increasing five phenolic acids related to monolignol biosynthesis, namely p-coumaric acid, chlorogenic acid, 1-O-sinapoyl-D-glucose, coniferyl alcohol, and ferulic acid, and sinapyl alcohol. Notably, P. notoginseng can establish a lignin barrier that restricted RKN to the infection site. In summary, P. notoginseng exhibited a potential ability to impede the further propagation of RKN through the accumulation or depletion of the compounds relevant to resistance within the phenylpropanoid and flavonoid pathways, as well as the induction of lignification in tissue cells.